2017
DOI: 10.18697/ajfand.78.harvestplus16
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy for biofortification: Building stakeholder support, integration into regional and national policies, and sustaining momentum

Abstract: Africa as a continent faces high prevalence of micronutrient deficiencies such as vitamin A, iron, and zinc. Biofortification offers a dietary agriculture-based strategy that has shown potential to address selected micronutrient deficiencies. This chapter describes how advocacy for biofortification by HarvestPlus and its partners has been structured, including a mix of evidence generation and sharing, stakeholder mapping, promotion to change attitudes, and efforts towards establishing Codex Alimentarius standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…as one of the focus crops (Covic et al, 2017). This was the first time biofortification was called for in an AU document, albeit not by name.…”
Section: To 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…as one of the focus crops (Covic et al, 2017). This was the first time biofortification was called for in an AU document, albeit not by name.…”
Section: To 2008mentioning
confidence: 99%
“…By 2011, momentum for a nutrition focus within CAADP was growing. (Covic et al, 2017). Baskets (BNFB) project.…”
Section: To 2013mentioning
confidence: 99%
“…Biofortification requires high adoption by both farmers and community. Indeed, the visibility of traits and infrastructures are critical to technology adoption [59,60]. Biofortified crops with visible traits such as orange-fleshed sweet potatoes and golden rice requires that producers and consumer accept these changes in addition to claimed nutritional potentials [59].…”
Section: Gaps In Knowledge and Practices Limiting Agriculture To Imprmentioning
confidence: 99%
“…So far, no accepted standards as per Codex Alimentarius for biofortified crops which is necessary for formal and legal integration into regulations to inform policy makers and provide directions for monitoring and evaluation [57,60,69]. Indeed, several questions for nutrients bioavailability and efficacy of biofortified crop are opening possibilities for further research [72,73].…”
Section: Gaps In Knowledge and Practices Limiting Agriculture To Imprmentioning
confidence: 99%
“…Bio-fortification is relatively a new technology, which is being promoted worldwide to combat hidden hunger (undernutrition), which is as a result of most communities relying on staple foods, which lack some nutrients resulting in increased incidence of malnutrition (Machida et al, 2014). It has been scientifically reported that bio-fortification is feasible without compromising agronomic productivity for crops such as maize; with high protein quality and vitamin A, that is QPM and pro-vitamin A maize, respectively (Andersson et al, 2017;Covic et al, 2017;Potrykus, 2017); hence bio-fortification is the way to go. Bio-fortified crops such as QPM have been developed to fight the problem of PEU in maize dependent communities such as the SSA.…”
Section: Protein-energy Management Strategiesmentioning
confidence: 99%